Cancer cell membrane-wrapped nanoparticles for cancer immunotherapy: A review of current developments - Jiang, Qi; Xie, Mixue; Chen, Ruyin; Yan, Feifei; Ye, Chanqi; Li, Qiong; Xu, Shuaishuai; Wu, Wei; Jia, Yunlu; Shen, Peng; Ruan, Jian (Frontiers in Immunology, 2022)
Background: As the forefront of nanomedicine, bionic nanotechnology has been widely used for drug delivery in order to obtain better efficacy but less toxicity for cancer treatments. With the rise of immunotherapy, the combination of nanotechnology and immunotherapy will play a greater potential of anti-tumor therapy. Due to its advantage of homologous targeting and antigen library from source cells, cancer cell membrane (CCM)-wrapped nanoparticles (CCNPs) has become an emerging topic in the field of immunotherapy. Key scientific concepts of review: CCNP strategies include targeting or modulating the tumor immune microenvironment and combination therapy with immune checkpoint inhibitors and cancer vaccines. This review summarizes the current developments in CCNPs for cancer immunotherapy and provides insight into the challenges of transferring this technology from the laboratory to the clinic as well as the potential future of this technology. Conclusion: This review described CCNPs have enormous potential in cancer immunotherapy, but there are still challenges in terms of translating their effects in vitro to the clinical setting. We believe that these challenges can be addressed in the future with a focus on individualized treatment with CCNPs as well as CCNPs combined with other effective treatments.